KAWUNG BATIK'S DESIGN IN LEATHER CLOTHING STREETWEAR STYLE AS A CULTURAL PRESERVATION EFFORT - Mochammad Charis Hidayahtullah; Eka Legya Frannita; Intan Nurhayati; Ahsan Afriza Rahmadani; Desy Karina Putri (Politek ATK Yogyakarta Press, 2024)
The era of globalization has caused foreign products/cultures to enter Indonesia, this has made local batik and leather crafts ready to compete and develop. This research aims to preserve kawung batik culture and leather crafts so that they are competitive in local and international markets. The Research and Development (R&D) method is considered the most appropriate because it consists of research, planning, and product development stages. The results of the research stage selected kawung beton batik because it has the best philosophy and aesthetics. Kawung beton has a philosophy and awareness that good deeds should not be displayed/flexed because they can cause body dysmorphia/anxiety in society. The analysis results at the planning and product development stage showed that wearable and streetwear-style clothing products are by the character of Gen Z consumers who are brave, assertive, rebellious, indifferent, and prioritize comfort. This recommended design for a combination of leather and batik materials is liked by Gen Z consumers so that efforts to preserve culture and leather MSMEs can further develop and compete in the market.